Teacher of the Department of Social and Humanities Uzbek State University of Physical Culture and Spor - Xurshitovna, Inagamova Feruza; Rahimbabaeva, N.A.; Abdullahanova, G.; Alimatova, N.; Kudratova, U. (International Journal of Psychosocial Rehabilitation, 2020)
This article presents a philosophical and conceptual analysis of the concept of nonviolence. The dialectics of violence and nonviolence have been thoroughly analyzed. The opinions of many scholars in this area have been analyzed. The issue of use and non-use of force is now considered to be one of the major but major issues in society.